(3EVGAI GdGOehS hQjGVI GdTehS aj GUWdGM UGMH GdbGehSs - (3eMeO Hf YHO Gddg Hf GdMGL EHQGgje GdYdhjs; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi Lejd UfYI CeG HYO aEfg bO jUd dj eWGdYI GdbGehS hGSJbQGFI heHGMKI s
(3BNQgG (B:s
(3hGdYTGA hGdZWGA (B,(3GdhcGA agPg cdgG HGdcSQ hEf CWdb GdeDda HYVgG s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs